Pengaruh Penerapan Gaya Mengajar Komando Terhadap Peningkatan Gerak Dasar Passing Bawah Dalam Permainan Bola Voli Pada Siswa SMP N 4 Ratahan - Panji Yudha Lumepa; Tony Pandaleke; Djajaty M. Lolowang (STIKES Columbia Asia Medan, 2025)
This study aims to investigate the effect of the command teaching style on the improvement of underhand passing skills in volleyball among eighth-grade students at SMP Negeri 4 Ratahan. A quantitative experimental method was used with a pretest-posttest control group design. Twenty students were randomly divided into an experimental group, which received instruction using the command teaching style, and a control group that received no special treatment. Data were collected through performance tests before and after the intervention and analyzed using t-tests. The results indicated a significant improvement in the underhand passing skills of students taught using the command style compared to those in the control group. These findings suggest that the command teaching style is effective for improving basic motor skills that require precision and consistency, such as underhand passing in volleyball. The results provide useful insights for physical education teachers seeking structured and effective instructional strategies to enhance technical skills in sports.